A prospective study of clinical profile in patients of palmoplantar dermatoses - Pragya A Nair; Nilofar G Diwan; Rochit Singhal; Rita V Vora (Wolters Kluwer Medknow Publications, 2017)
Background: Palms and soles are the readily visible areas of the body that are affected in various dermatoses. This may have considerable concern to the patient and can cause diagnostic dilemma. Moreover, palmoplantar dermatoses also limit our day to day activities with a significant impact on quality of life. Aim: To study the clinical profile of patients suffering from palmoplantar dermatoses at a tertiary care centre. Patients and Methods: A prospective observational study was carried out from June 2014 to May 2015 in the Department of Dermatology, Venerology and Leprosy at a rural tertiary care centre after taking approval from the institutional ethical committee. In total, 202 cases were enrolled. The study was analyzed using Chi-square test. Results: A total of 202 patients were enrolled, among which 53.46% were males. The most common age group affected was 17-40 years (42.57%). Duration of less than 1 month was seen in 31.7% cases whereas 29.7% showed seasonal variation. The most common chief complaint was itching (69.8%). Palmoplantar psoriasis was the most common dermatosis with 28.22% cases, followed by keratinizing disorders with 26.72% cases. Palms were involved in 66.34% cases, soles in 69.30%, and both palms and soles in 37.12% cases. Other body parts were involved in 15.34% of the cases. Diabetes and hypertension were common comorbid conditions seen in 11.4% of the cases each. Conclusion: Palmoplantar psoriasis was the most common disorder affecting palms and soles followed by palmoplantar keratoderma.